Strategi Pemasaran Syariah Dalam Meningkatkan Minat Beli Konsumen Di Kafe Safira Desa Peninjauan Kecamatan Maro Sebo Ulu Kabupaten Batang Hari - Elly Jupridah; Maulana Yusuf; Solichah Solichah (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This research aims to (1) determine sharia marketing strategies in increasing consumer buying interest carried out by Safira cafe owners in the reviewing village of Mare Sebo Ulu sub-district, Batang Hari district. (2) To find out the obstacles faced in efforts to increase consumer buying interest at Safira Cafe. This research uses descriptive qualitative methods. The data collection technique in this research uses observation, interview and documentation techniques. The theory used in this research is the theory put forward by Abuznaid formulating the definition of sharia marketing, namely, wise decisions in order to satisfy customer needs through good behavior, providing healthy products or services (halalan thoyyibah) with the approval of both parties (seller and buyer). ) in order to achieve material and spiritual prosperity, this world and the hereafter through an ethical world. Apart from that, the theory used by Kotler, marketing is a way in which companies involve consumers, build good relationships with consumers and create value for consumers, so as to get good value or response from consumers in increasing profits and consumer feedback. The 4P marketing strategy used is, product, price, place and promotion. The results of this research show that, the marketing strategy carried out by Safira Cafe to increase revenue is with product strategies starting from improving the quality of the products presented, product health, product cleanliness and product halal. Pricing strategy, Safira Cafe has set affordable, relatively cheap prices. The prices offered by Safira Cafe are affordable and cheap in accordance with the economy of the community in the review village and are suitable for all teenagers and adults. Place strategy, safira cafe prioritizing the cleanliness of the place and consumer comfort while at the Safira Cafe. Promotional strategy, Safira Cafe does not promote via social media, only promotes by word of mouth, but quite a few people already know about the existence of Safira Cafe. Meanwhile, the income earned by Safira Cafe is still relative or fluctuating, namely depending on the number of visitors.